The space book from the beginning to the end of time, 250 milestones in the history of space & astronomy - Bell, Jim 1965- (New York, NY Sterling, 2013)
Presents a series of 250 significant events in the history of astronomy and space exploration, from the original formation of the galaxies, to the space mission to the planet Mars, to speculation about the end of the universe --
Birth of the universe -- Observing the heavens -- The Space Age -- Our future
Includes bibliographical references (p. 518-525) and index
1
Keywords: Cosmology -- History; Cosmology; Physics -- History; Universe